Slope Detection Based on Grating Sensors - Huang, Lin; Liu, Fengyin; Li, Jun (International Journal of Online and Biomedical Engineering (iJOE), 2018)
Because slope detection is often subject to various electromagnetic disturbances and weather limitations, there is an urgent need to develop a monitoring system that has the advantages of strong anti-electromagnetic interference capability, long service life, and small external environmental impact.Based on this demand, a real-time slope monitoring system based on fiber Bragg grating angle, crack, and osmotic pressure sensors is designed.The design idea is to use the sensitivity of FBG to the external stress, and the angle and crack penetrating pressure information are obtained from the offset of wavelength in different sensors to determine the stability of the slope.The design and implementation of the FBG slope monitoring system can better solve the existing problems in the slope monitoring, improve the ability to predict dangers, and strengthen the safety monitoring capability.The utility value of the system is high.